STUDI KUALITATIF PENDEKATAN METODE PEMBELAJARAN KETERAMPILAN REGULASI DIRI DENGAN PERSPEKTIF MINDFULNESS PADA PASIEN GANGGUAN CEMAS DI KLINIK TALENTA CENTER BEKASI - Rika Nafratilofa Dwi Aprillia, (2022)
Anxiety disorder is a mental condition that is frequently identified primarily in adolescents. Anxiety disorder regulation may be performed through medications. In practice, however, the possibility of recurrence still prevails. Therefore, an additional regulation method such as a self-regulation learning skill method with a mindfulness perspective is required. This method can be exercised continuously and have a long-term impact on reducing anxiety. The research aims to identify whether anxiety disorder symptoms can be reduced and whether self-regulation capacity can be improved in adolescents with anxiety disorders using the self-regulation skills learning method with a mindfulness perspective. An adolescent female patient with anxiety disorder performed a selfregulation skill learning method with a mindfulness perspective in Talenta Center Clinic Bekasi. Data was collected through interviews and questionnaires, and descriptive processing. In adolescent patients with anxiety disorder, using the self-regulation skill method with a mindfulness perspective as therapy may reduce the anxiety disorder symptoms and improve the self-regulation capacity. The evidence showed that the anxiety symptoms were reduced, and constant anxiety about self-harm was controlled. Furthermore, the patient's selfregulation capacity was improved and resulted in better mindful emotional management upon an occurrence of an event